FRAMING COVID-19: HOW FACT-CHECKING CIRCULATES ON POLITICAL FACEBOOK - Recuero, Raquel (AoIR Selected Papers of Internet Research, 2021)
This abstract compiles the results of a research on how the political framing of fact-checking posts about Covid-19 may influence their circulation on Facebook. Our research is based on a dataset of 460 fact-checking posts published on politically aligned Brazilian Facebook pages/groups. We used frame analysis to discuss how these posts share fact-checking links. Our results point to the right-wing affiliated groups/pages sharing more fact-checking than left-aligned ones, but using framing strategies to subvert fact-checking content to support their beliefs.These results show that fact-checking does circulate on political Facebook groups/pages that share disinformation (and they circulate on right-wing and conservative ones), but it is used to reinforce their discourse, rather than debunk it.